Neural Androgen Receptors Modulate Gene Expression and Social Recognition But Not Social Investigation - Karlsson, Sara A.; Studer, Erik; Kettunen, Petronella; Westberg, Lars (Frontiers in Behavioral Neuroscience, 2016)
The role of sex and androgen receptors (ARs) for social preference and social memory is rather unknown. In this study of mice we compared males, females and males lacking ARs specifically in the nervous system, ARNesDel, with respect to social preference, assessed with the three-chambered apparatus test, and social recognition, assessed with the social discrimination procedure. In the social discrimination test we also evaluated the tentative importance of the sex of the stimulus animal. Novel object recognition and olfaction were investigated to complement the results from the social tests. Gene expression analysis was performed to reveal molecules involved in the effects of sex and androgens on social behaviors. All three test groups showed social preference in the three-chambered apparatus test. In both social tests an AR-independent sexual dimorphism was seen in the persistence of social investigation of female conspecifics, whereas the social interest towards male stimuli mice was similar in all groups. Male and female controls recognized conspecifics independent of their sex, whereas ARNesDel males recognized female but not male stimuli mice. Moreover, the non-social behaviors were not affected by AR deficiency. The gene expression analyses of hypothalamus and amygdala indicated that Oxtr, Cd38, Esr1, Cyp19a1, Ucn3, Crh and Gtf2i were differentially expressed between the three groups. In conclusion, our results suggest that ARs are required for recognition of male but not female conspecifics, while being dispensable for social investigation towards both sexes. In addition, the AR seems to regulate genes related to oxytocin, estrogen and William’s syndrome.